1986
DOI: 10.1007/bf00237403
|View full text |Cite
|
Sign up to set email alerts
|

Development of the spinal tract of the trigeminal nerve and its relation to early fetal behavior in rats under normal and hypothyroid conditions

Abstract: The effects of hypothyroidism on the development of the spinal tract of V and its relation to early fetal behavior were studied in rats from day 16 through day 20 of gestation. Hypothyroidism was induced by the administration of 0.5% Propylthiouracil mixed with rat diet beginning from day seven through term. The thyroid glands of treated and untreated control fetuses of the same age groups were examined in histologic sections. The position, size, and caudal extent of the ophthalmic and maxillomandibular divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The functional consequences of this convergence have been demonstrated in several studies investigating the influence of trigeminal input on neck muscles. Developmental studies of human and rat fetuses have demonstrated that perioral stimuli elicit head movements along with oral responses (Humphrey, 1964;Narayanan et al, 1986). Sternocleidomastoid and trapezius contraction can be elicited by direct stimulation of the Gasserian ganglion of the adult cat (Green et al, 1957).…”
mentioning
confidence: 99%
“…The functional consequences of this convergence have been demonstrated in several studies investigating the influence of trigeminal input on neck muscles. Developmental studies of human and rat fetuses have demonstrated that perioral stimuli elicit head movements along with oral responses (Humphrey, 1964;Narayanan et al, 1986). Sternocleidomastoid and trapezius contraction can be elicited by direct stimulation of the Gasserian ganglion of the adult cat (Green et al, 1957).…”
mentioning
confidence: 99%
“…The final PTU dosage used in the present study was selected from different doses (0.0001-0.5%) tested in our laboratory according to previous studies (Legrand, 1967(Legrand, , 1986Battie and Verity, 1979;Narayanan et al, 1986;Lomax and Robertson, 1992). These pregnant dams were kept in individual cages and fed with standard cube diet.…”
Section: Materials and Methods Animal Treatment: Induction Of Hypothymentioning
confidence: 99%
“…, 1995). Neuro‐anatomical studies have established that the spinal tract of the trigeminal nerve can be traced down the dorsal horn of the upper cervical cord (Narayanan, Narayanan & Browne, 1986), and that some neurones in the trigeminal sensory nuclei synapse directly on the motorneurones of the dorsal neck muscles (Sumino et al ., 1981; Alstermark et al ., 1992).…”
Section: Introductionmentioning
confidence: 99%